The effect of beet juice consuming to the tension of hypertension patients - Agnia Dwi Nandani; Mira Sofyaningsih (ARGIPA (Arsip Gizi dan Pangan), 2019)
Hypertension can occur in all ages. Factors that can cause high blood pressure including genetics, being overweight, lack of physical activity, stress, high sodium intake, and lack of fiber intake. Beetroot is one of the vegetables that contains fiber and nitrates which have the effect of lowering blood pressure. The purpose of this study was to know the effect of consuming beetroot juice to the change in blood pressure. The type of this research is experimental with the design of one group pre test post test. The number of respondents were 15 people with systolic blood pressure > 129 mmHg and or diastolic blood pressure > 80 mmHg. Respondents were given 250 grams of beetroot juice once a day for 7 consecutive days. The beetroot juice given is made of 150 grams of beetroot, 100 ml of water, and 1 tablespoon of lime juice. The result showed that there was an average decreasing in systolic blood pressure of 10.41 mmHg and diastolic blood pressure of 8.94 mmHg. Consuming of beetroot juice can significantly reduce systolic blood pressure and diastolic blood pressure in hypertensive patients in Posbindu Mawar Merah and Merah Delima. Keywords: Hypertension, Beetroot Juice, Blood Pressure